Utilization Of Fuzzy Time Series Method Of Analyzing Changes In Rice Prices Throughout The Year In East Java - Sehman, Sehman (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The research aims to analyze the vertical transmission of rice selling prices from the producer (miller) level to the consumer and analyze what factors influence the formation of rice prices at the producer (miller) level in east java province. The main data used is 2023 data from january to september 2023 with a sample of each rice price in the district/city in east java province, while for the analysis of price formation factors using monthly data on rice prices at the producer (miller) level, rice prices in consumer level, rice consumption, price of imported rice 2. The method used in this research is a descriptive research method with a quantitative approach. The analysis tool used is fuzzy time series. The research results found that the rice price transmission pattern in east java province was symmetrical. In the short term, the rice price transmission pattern is asymmetric, meaning that there is a delay or indirect price transmission mechanism between producers and consumers, and in the long term, this means that consumer prices are transmitted directly to producer prices. (milling). Factors that influence the price of rice at the milling level in east java province are consumer prices, imported rice prices, rice consumption, and climate.